Peran Kinerja Karyawan Yang Dipersepsikan Oleh Pelatihan, Kompensasi, Dan Lingkungan Kerja PT Perkasa Karya Mandiri Di Kota Batam - Somi Balun, Bernardus (Tractare: Jurnal Ekonomi-Manajemen, 2023)
This study aims to determine the effect of training, compensation and work environment on the performance of employees of PT Perkasa Karya Mandiri in Batam either partially or simultaneously. The type of research applied in this research is quantitative research, the population in this study is 127 people. Researchers used a systematic sampling technique with 63 respondents. The data collection technique uses a questionnaire and is distributed via the Google form. Data analysis using SPSS version 26 research results found that the training variable has a tcount value of -0,802 ttable 2,001 and a significance value of 0,000 < 0,05, then H0 is accepted and Ha is rejected. then H0 is rejected and Ha is accepted, the work environment variable has a tcount of 3,996 ttable 2,001 and a significance value of 0,000 < 0,05 then, H0 is rejected and Ha is accepted. the three variables namely training, compensation and work environment together have a Fcount of 32,723 Ftable 2,76 and a significance value of 0,000 < 0,05. This shows that simultaneously training, compensation and work environment have a positive and significant effect on the performance of employees of PT Perkasa Karya Mandiri in Batam. And the coefficient of determination (R2) shows that the independent variables contribute 60,6% while the remaining 39,4% is influenced by other factors not examined in this study. Keywords: Training, Compensation, Work Enviroment, Employee Performance